EPEN-53. C11orf95-RELA REPROGRAMS 3D EPIGENOME IN SUPRATENTORIAL EPENDYMOMA. (4th December 2020) - Zhu, Jacqueline Jufen; Jillette, Nathaniel; Li, Xiao-Nan; Cheng, Albert; Lau, Ching
Abstract: Ependymoma is the third most common malignant brain tumor in children. However, there is no effective chemotherapy identified and treatment is limited to surgery with or without adjuvant radiation therapy currently. Thus, to develop targeted therapy based on the underlying biology is an urgent need. Since 2014, C11orf95-RELA fusion was found to be the most recurrent structural variation in approximately 70% of supratentorial ependymomas (ST-EPN), but the molecular mechanisms of oncogenesis are unclear. Here we utilized HEK293T transgene models and a ST-EPN cell line to investigate the epigenomic changes and transcriptional regulations by C11orf95-RELA fusion. By applying ChIP-seq and HiChIP approaches, we found C11orf95-RELA is a novel transcription factor that recognizes a specific DNA motif dictated by the C11orf95 component while the RELA component is required for driving the expression of ependymoma-associated genes such as CCND1 and L1CAM . Moreover, C11orf95-RELA modulates chromatin states and mediates chromatin interactions, leading to transcriptional reprogramming in ST-EPN cells. Multiple signaling pathways such as Notch signaling and G-protein signaling are identified to be involved in ST-EPN development. Our findings provide important characterization of the molecular underpinning of C11orf95-RELA fusion and shed light on potential therapeutic targets for C11orf95-RELA subtype ependymoma.